Perspektif Hukum Islam Tentang Konsep Penguasaan Tanah - Mohammad Muhibbin (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2017)
Everything in the earth belongs to Allah. Human are given an authority by Allah as kholifah to prosper the earth as the human’s responsibility to Allah. Whoever have/authorize a land considered having a mandate from Allah should comprehend the intended law established by Allah so that what the human do as a kholifah toward the authority and ownership of land in their territorial as the essence of transfer from Allah in order to manage, watch, distribute, and guide the use of land in accordance with Allah’ aim to create the earth for the sake of human’s prosperity and of public goodness (al-maslahah al-’âmmah).